Haemoglobin A1c variability is a strong, independent predictor of all‐cause mortality in patients with type 2 diabetes. Issue 8 (19th April 2018) - Orsi, Emanuela; Solini, Anna; Bonora, Enzo; Fondelli, Cecilia; Trevisan, Roberto; Vedovato, Monica; Cavalot, Franco; Gruden, Gabriella; Morano, Susanna; Nicolucci, Antonio; Penno, Giuseppe; Pugliese, Giuseppe; et al.
Abstract : Aims: To evaluate various measures of haemoglobin (Hb) A1c variability, compared with average HbA1c, as independent predictors of mortality. Materials and Methods: The Renal Insufficiency And Cardiovascular Events Italian multicentre study enroled 15 733 patients with type 2 diabetes from 19 diabetes clinics during 2006‐2008. A total of 3 to 5 HbA1c measures, obtained during the 2‐year period before enrolment, were available from 9 centres (8290 patients) and were used to calculate average HbA1c (HbA1c ‐MEAN) and HbA1c variability, measured as intra‐individual standard deviation (HbA1c‐SD), SD adjusted for the number of HbA1c assessments (HbA1c‐AdjSD) and coefficient of variation (HbA1c‐CV), that is, the HbA1c‐SD to HbA1c‐MEAN ratio. Vital status on October 31, 2015 was retrieved for 8252 patients (99.5%). Results: The measures of HbA1c variability increased according to quartiles of HbA1c‐MEAN and vice versa. HbA1c‐MEAN and measures of HbA1c variability were associated with all‐cause mortality; however, the strength of association of HbA1c‐MEAN was lower than that of HbA1c ‐SD, HbA1c‐CV or HbA1c‐AdjSD, and disappeared after adjusting for confounders and any of the measures of HbA1c variability. Mortality increased with quartiles of HbA1c‐MEAN, HbA1c ‐SD, HbA1c‐CV and HbA1c‐AdjSD, but only the association with HbA1c variability measures remained after adjustment for confounders and/or each other measure. In the fully adjusted model, mortality risk was lower for HbA1c‐SD below the median and higher for HbA1c‐SD above the median, regardless of whether HbA1c‐MEAN was below or above the median. Conclusions: HbA1c variability is a strong, independent predictor of all‐cause mortality in type 2 diabetes and appears to be even more powerful than average HbA1c in predicting mortality.